Modeling the coevolution of international and domestic institutions: Alliances, democracy, and the complex path to peace. (May 2016) - Warren, T Camber
While much previous research has examined the relationship between interstate military alliances and the structure of domestic regimes, existing findings point in contradictory directions. Some have argued that democracies attract each other as alliance partners, and thereby generate international peace as a consequence of their domestic regime type, while others have argued that the causal relationship is reversed, and that international pacification creates the necessary space for international alliances and domestic democratization. To disentangle this difficult empirical relationship, this article presents an empirically grounded simulation model of the dynamic coevolution of interstate military alliances, international conflict, and domestic democratization, demonstrating a statistical approach which accounts both for the complex interdependencies generated by coevolving multiplex networks of interstate ties and for their reciprocal influence on the coevolution of domestic political regimes, over the period 1920–2000. The results show that international institutions and domestic institutions are mutually constituted, with both 'selection' effects and 'influence' effects operating simultaneously. In particular, the evidence indicates that states with similar regimes are more prone to ally with each other, mutually democratic dyads are less inclined to engage in militarized disputes, and states that form international alliances with democratic partners are more likely to develop domestic democratic institutions. Tests of out-of-sample predictive accuracy, across multidecade prediction windows, further demonstrate that the coevolutionary model consistently outperforms specifications that ignore coevolutionary effects, in predicting subsequent patterns of military alliances, military conflict, and domestic democratization.